Identity issues in burial mound research and interpretation - Potrebica, Hrvoje (Array, 2008)
The paper explores different aspects of burial mound research and interpretation related to identity and how those aspects relate to the outcomes of scientific analysis. The primary level of discussion includes the percieved identity of the buried individual(s) within the contemporary local community as well as the historical perception of such monuments. The second level analyses limitations and possibilities of establishing different kinds of identity through archaeological methodologies (gender, age, kinship, social (individual-family-clan-community), ethnic, etc.) including the excavation process, analysis of spatial features, laboratory analyses, and contextual analysis of material remains.